Платоновские традиции в творчестве Сергея Залыгина последних лет - Rudziewicz, Irena (Acta Polono-Ruthenica, 2008)
In the article an attempt was made to present Sergey Zalygin’s attitude to Platonov’s literally output. On the basis of a comparative analysis of both writers’ selected works, relationships, form soft effect and particular element soft the influence of Platonov’s poetica on Zalygin’s output wereshow. Special attention was paid to fantasy and fairylike aspects manifesting themselves under theinfluence of tradition on the part of the Russian classic.